Determinants of profitability and their impact on financial performance: a case study in selected listed manufacturing companies in colombo stock exchange (cse) - Anojan, V. (University of Jaffna, 2016)
The focus of this study is to find out the significant impact of determinants of the profitability on financial performance of selected listed manufacturing companies and identify the relationship among determinants of the profitability and financial performance of the selected listed manufacturing companies in Colombo Stock Exchange (CSE) from the financial year 2010/11 to 2014/15. Determine the right, suitable and proper capital structure is the major task of the firms here capital structure includes two major things such as equity and debt capital. Capital structure is vital in determining the return on equity (ROE). Liquidity is also one of the major components in determining the profitability of any firms. Liquidity much be needed for day to day financial transactions of the firms. Firms' growth is also determining the firm's profitability. Descriptive, regression and correlation analysis 2 were performed in this study. Regression results revealed that there is significant (R = 0.754/ 75.4%) impact of determinants such as capital structure, firms' growth and liquidity position on the profitability of the selected listed manufacturing companies. Correlation results confirmed that there is significant relationship among selected listed manufacturing companies' capital structure, firms' growth, liquidity position and profitability. Finally as a researcher suggests that every selected listed manufacturing firm should give key focus on its firm's growth, capital structure and liquidity position to enhance its profitability in the future.
Keywords: Capital structure; Firm's growth; Financial performance; Liquidity position; Listed manufacturing firms